Corneal Infection Associated with Diabetes: A Case Study & Literature Review - Miller, S.; Pishgahi, M.; Ghanim, M.; Fongue, S.; Alhasana, O.H.; Najeemuddin, S.; Lopez, A.C.; Gunaseelan, L.; Jamshaid, A.; Charles, P.; Hamid, M. (Journal of Ocular Diseases and Therapeutics, 2020)
A 54-year-old woman with a history of type 2 diabetes presented with concern for sudden eye pain, photophobia, and redness of the eye. History, physical examination and comprehensive lab tests, yielded a diagnosis of corneal keratopathy. She responded poorly to the initial management of moxifloxacin 5% and homatropine 2%. A multi-faceted approach involving strict glycemic control and antibiotic therapy was then adopted. Through dietary management and pharmacotherapy, the patient’s clinical disposition improved, highlighting the importance of glycemic control when managing diabetic keratopathy.